2020
DOI: 10.1155/2020/9684792
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Hormonal Profile of Athletes following a Combat Sports Performance

Abstract: Background and Study Aim. Stimulation of the sympathetic nervous system and the hypothalamic-pituitary-adrenal axis are a crucial mechanism of adaptation to physical exercise, in particular in combat sports. This study assesses changes of the relevant hormonal profiles upon performance in selected combat sports. Material and Methods. Participants (130 men practicing combat sports at a high level) were divided by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
(34 reference statements)
0
7
0
2
Order By: Relevance
“…Furthermore, seasonal variations did occur whereby s-T was significantly higher at PRE and POST compared to IN. Although no significant association was reported between training loads and any salivary measures, when coupled with higher training loads elevated testosterone may represent stimulation of the hypothalamic–pituitary–adrenal axis, one of the main mechanisms of adaptation to PRE training [ 59 ]. The current study shows a significant decrease in s-T at IN with similar findings reported in professional soccer players [ 4 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, seasonal variations did occur whereby s-T was significantly higher at PRE and POST compared to IN. Although no significant association was reported between training loads and any salivary measures, when coupled with higher training loads elevated testosterone may represent stimulation of the hypothalamic–pituitary–adrenal axis, one of the main mechanisms of adaptation to PRE training [ 59 ]. The current study shows a significant decrease in s-T at IN with similar findings reported in professional soccer players [ 4 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is one available study in the literature with a somewhat similar methodology evaluating serum BDNF levels in wrestling athletes. In that study, serum BDNF levels were increased after a fighting match (high intensity, duration 3 × 2 min) in an athlete group including judo, sumo, and wrestling [ 27 ]. In our study, wrestling athletes were submitted to a competition consisting of 2 periods for 2 × 3 min.…”
Section: Discussionmentioning
confidence: 99%
“…The HPA pathway induces a longer transient hormonal cascade leading to glucocorticoids (cortisol) release from the adrenal cortex [ 237 ]. Researchers have studied the close relationship between stress hormones and athletic performance [ 238 , 239 ], and it has been found that circulating catecholamine levels increase during exercise in healthy athletes [ 240 ]. Catecholamines have beneficial effects on the heart, skeletal muscle, and central nervous system in relation to exercise performance [ 241 ].…”
Section: Oxidative Stress and Athletic Antioxidant Statusmentioning
confidence: 99%